Acute fulminant hepatitis E virus genotype 3e infection: Description of the first case in Europe. (October 2014) - Festa, Stefano; Garbuglia, Anna Rosa; Baccini, Flavia; Panzuto, Francesco; Capobianchi, Maria Rosaria; Santino, Iolanda; Purchiaroni, Flaminia; Orgera, Gianluigi; Delle Fave, Gianfranco; Marignani, Massimo
Abstract Hepatitis E virus (HEV) is the most important causative agent of acute hepatitis in developing countries. The disease is usually characterized by a self-limiting, benign course. However, when particular conditions coexist (pregnancy, old age, pre-existing liver disease) it may run an unfavourable course. To date, 4 HEV genotypes have been described. Historically, in the Western world, HEV infection was considered a travel-related disease, however in the last 2 decades a great number of non-travel-related autochthonous cases have been described, more often related to genotype 3 or 4 and in the context of zoonosis. We report the case of an elderly Italian man with an acute fulminant HEV infection genotype 3e that developed in the context of pre-existing liver disease; this is the first case of an unfavourable outcome associated with subgenotype 3e. The potential pathogenicity of this subgenotype together with the influence of host-related risk factors are discussed.